2015
DOI: 10.1007/s10854-015-2813-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of annealing on microstructure of Co/Cu multilayers

Abstract: The microstructure evolution of magnetron sputtered Co/Cu multilayers induced by annealing has been investigated using X-ray diffraction and reflectometry, atomic force microscopy, and electron microscopy. The experimental results indicated that Co/Cu multilayers with an individual layer thickness of 2 nm showed a stable layer stacking until the annealing temperature reached 600°C. At that temperature, part of the initial {111} fibre texture transformed into {200} fibre texture. Columnar structure with a multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Reflectivity, arb.unit. Depth, nm close optical constant values is typical for an XRR study of Co/Cu systems [17,18]. Marszalek et al [19] reported that periodic multilayered Co/Cu structures grown by thermal sputtering are characterized by a strong smearing of interfaces at a level of 3 nm, which could additionally intricate studying of barriers in Co/Cu structures.…”
Section: Cu 4nm Cu 28nmmentioning
confidence: 93%
“…Reflectivity, arb.unit. Depth, nm close optical constant values is typical for an XRR study of Co/Cu systems [17,18]. Marszalek et al [19] reported that periodic multilayered Co/Cu structures grown by thermal sputtering are characterized by a strong smearing of interfaces at a level of 3 nm, which could additionally intricate studying of barriers in Co/Cu structures.…”
Section: Cu 4nm Cu 28nmmentioning
confidence: 93%